Politik Satu Dimensi: Tinjauan Kebijakan Kawasan Eko-Wisata Hutan Oeluan di Kabupaten Timor Tengah Utara [One-Dimensional Politics: Policy Review of The Oeluan Forest Ecotourism Area In North Central Timor] - Boro, Veronika Ina Assan; Satu, Innosensia; Tokan, Frans Bapa; Kosat, Emanuel (Jurnal Politica, 2023)
This study aims to review the pattern of resistance in the development policy of Oeluan Forest ecotourism. The protest is based on the community's respect for sacred springs. The theory cluster of 'One-Dimensional Politics' as an analytical knife examines political practices that mainstream the economic impact of tourism. This study uses a qualitative approach with the specification of a descriptive-explorative method. The results of the research show that efforts to reify the Oeluan Forest, a political strategy to approach the community in a neat and planned manner, have triggered deforestation and desacralization that are rife in East Nusa Tenggara. The urgency of indigenous peoples' business lies in proposing multidimensional politics in the policy corpus of the Oeluan Forest ecotourism area.AbstrakPenelitian ini bertujuan untuk meninjau corak resistensi dalam kebijakan pembangunan ekowisata Hutan Oeluan. Protes tersebut berlatar penghormatan masyarakat terhadap mata air yang disakralkan. Gugus teori 'Politk Satu Dimensi' sebagai pisau analisis mencermati praktik politik yang mengarusutamakan impak ekonomi pariwisata. Penelitian ini menggunakan pendekatan kualitatif dengan spesifikasi metode deskriptif-eksploratif. Hasil penelitian menunjukan upaya reifikasi Hutan Oeluan ialah strategi politik untuk mendekati masyarakat secara apik dan terencana telah memicu deforestasi dan desakralisasi yang marak terjadi di Nusa Tenggara Timur. Urgensi usaha masyarakat adat terletak pada mengajukan politik multidimensional dalam korpus kebijakan kawasan ekowisata Hutan Oeluan.